Online advertising: how the consumer goods speaks to women - Munira Hasjim, Muhammad Hasyim, Nursidah, (Opción, 2019)
This research discusses the phenomenon of the product ofconsumer goods to communicate with women online commercialadvertising. The method used is descriptive that try to describe thephenomenon of products interaction to women on onlineadvertisement. The results of this research show that for speaking towomen, online commercial advertising sells the social value, likelifestyle and family. In conclusion, one type of communication thatexists today besides interpersonal communication, organizationalcommunication, and mass communication is the communicationbetween humans and objects.